Fra bibelske til rabbinske opfattelser af askese: Jødedommens verdensbekræftende praksis - Schleicher, Marianne (Religionsvidenskabeligt Tidsskrift, 2016)
The purpose of this article is to supplement scholarly positions that define asceticism either as a matter of world renouncement and elitist self-exclusion from the world or as always oriented toward transcendent goals or practices of improvement because these positions run the risk of overlooking moderate kinds of asceticism. Israelite, early Jewish, and early Rabbinic Jewish religion are replete with examples of moderate asceticism where both men and women are encouraged to engage in abstinence and self-training in order – not to improve, but – to preserve a religious tradition. With Steven D. Fraade’s definition of asceticism as a departing point, the article examines abstinence and self-training in the Hebrew Bible, early Jewish and early Rabbinic literature. The author discerns three types of moderate asceticism: that of the priest, the layperson, and the hero/-ine. These three types complement each other in a shared effort to preserve divine blessings in this world and thereby the preservation of Israelite-Jewish tradition.